Health Risks to Ecological Workers on Contaminated Sites - The Department of Energy as a Case Study - J, Burger; M, Gochfeld (Journal of community medicine & health education, 2016)
At most contaminated sites the risk to workers focuses on those 'hazardous waste workers' directly exposed to chemicals or radionuclides, and to the elaborate approaches implemented to protecting their health and safety. Ecological workers generally are not considered. To explore the risks to the health and safety of ecological workers on sites with potential chemical and radiological exposures before, during or after remediation of contamination. To use the U.S. Department of Energy as a case study, and to develop concepts that apply generally to sites contaminated with hazardous or nuclear wastes. Develop categories of ecological workers, describe their usual jobs, and provide information on the kinds of risks they face. Ecological activities include continued surveillance and monitoring work on any sites with residual contamination, subject to institutional controls and engineered barriers following closure as well as the restoration. The categories of ecological workers and their tasks include 1) Ecological characterization, mapping and monitoring, 2) biodiversity studies, 2) Contaminant fate and transport, 3) On-going industrial activities 4) Remediation activities (environmental management), 5) Environmental restoration, 6) Post-cleanup surveillance and monitoring, and 7) Post-closure future site activities. There are a set of functional activities that can occur with different frequencies and intensities, including visual inspection, collecting biological samples, collecting media physical samples, collecting biological debris, restoration planting, and maintaining ecosystems. Ecological workers face different exposures and risks than other environmental cleanup workers. Many of their tasks mimic shift work with long hours leading to fatigue, and they are exposed to biological as well as chemical/radiological hazards. DOE and other entities need to examine the risks to ecological workers on site with an eye to risk reduction.